2009
DOI: 10.1007/s00268-009-0018-2
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Perioperative Rehabilitation for Colonic Surgery in the Elderly

Abstract: Although the overall morbidity did increase with age, it was still less when compared to that of historical groups with traditional care. Therefore, multimodal perioperative rehabilitation should be recommended for the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 43 publications
1
43
2
1
Order By: Relevance
“…Six of the nine studies reported lower readmission rates for the older group (13,23-25, 27,28), but this was only a statistically significant lower rate in one study (27).…”
Section: Studies Comparing Older To Younger Patients In Erasmentioning
confidence: 88%
See 4 more Smart Citations
“…Six of the nine studies reported lower readmission rates for the older group (13,23-25, 27,28), but this was only a statistically significant lower rate in one study (27).…”
Section: Studies Comparing Older To Younger Patients In Erasmentioning
confidence: 88%
“…Mortality rates varied greatly across the 6 studies which reported on them (22)(23)(24)(25)27,28). In the 4 studies where mortality rates were low, there was little difference between age groups (22,24,27,28).…”
Section: Studies Comparing Older To Younger Patients In Erasmentioning
confidence: 99%
See 3 more Smart Citations